PENYELESAIAN KREDIT MACET TERHADAP HAK TANGGUNGAN (PENELITIAN DI KOPERASI GUNA ARTHA MESARI) - I Gusti Agung Rai Adiaksa Negara (Jurnal AKSES, 2020)
The function of a cooperative here is to make it prosperous by providing capital or credit loans to advance the community's economy. Submission of credit agreement The form and material of the credit agreement between the bank and the cooperative are not the same. Loans do not have a generally accepted form, it's just that in the terms of the terms specified to be used in the agreement, the amount and time limit of the loan, as well as loan repayment, interest and penalties if the debtor is negligent. Collateral used by cooperatives in general is a material guarantee. Implementation of Bad Credit Execution for Dependents in the Cooperative Guna Artha Mesari, Nonperforming loans or nonperforming loans is a risk that is given in every credit extension by cooperatives.